2023
DOI: 10.3389/fnmol.2023.1275924
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying physical exercise-induced brain BDNF overproduction

Marina Cefis,
Remi Chaney,
Julien Wirtz
et al.

Abstract: Accumulating evidence supports that physical exercise (EX) is the most effective non-pharmacological strategy to improve brain health. EX prevents cognitive decline associated with age and decreases the risk of developing neurodegenerative diseases and psychiatric disorders. These positive effects of EX can be attributed to an increase in neurogenesis and neuroplastic processes, leading to learning and memory improvement. At the molecular level, there is a solid consensus to involve the neurotrophin brain-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 244 publications
1
7
0
Order By: Relevance
“…In summary, physical activity has been described as one of the most effective nonpharmacological approaches to lower blood pressure and prevent cardiovascular disease and deficits in brain function. 15 The current study supports the concept that exercise has beneficial effects on elements of vascular biology and blood pressure. The findings suggest such protection may be mediated, in part, via effects on AKAP150-dependent protein interactions and signaling.…”
Section: See Accompanying Article On Page 1202supporting
confidence: 83%
“…In summary, physical activity has been described as one of the most effective nonpharmacological approaches to lower blood pressure and prevent cardiovascular disease and deficits in brain function. 15 The current study supports the concept that exercise has beneficial effects on elements of vascular biology and blood pressure. The findings suggest such protection may be mediated, in part, via effects on AKAP150-dependent protein interactions and signaling.…”
Section: See Accompanying Article On Page 1202supporting
confidence: 83%
“…The crucial role of BDNF in the positive effects of EX on the brain [24][25][26] is well established, as in animal studies, anti-BDNF strategies reversed the cognitive benefits associated with EX [5,27,28], while in humans, the val66met polymorphism associated with a defect in activity-dependent regulated BDNF secretion, attenuated the cognitive benefits of EX [29][30][31]. While neuronal activity via calcium influx and neurotransmitter release and hemodynamic pathway through elevation of cerebral blood flow have long been considered as dominant mechanisms to increase cerebral BDNF expression [32], the humoral/endocrine pathway has recently been reported to play a considerable role in cerebral BDNF production in both rodents and humans [12], highlighting muscle FNDC5 production and irisin secretion [15].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF has strongly been linked to epilepsy during epileptogenesis as well as influencing excitability and connectivity in the adult brain [48] , [49] , [50] . Additionally, BDNF has been shown to increase in response to exercise [20] , [51] , while studies have also shown that BDNF expression can vary depending on the exercise intensity and type [21] , [52] . Serum IL-6 is a pro-inflammatory cytokine typically present at low levels in the brain but can be increased with seizures [53] .…”
Section: Discussionmentioning
confidence: 99%